Building global products and competing in innovation: the role of Chinese university spin-outs and required innovation capabilities. (1st January 2014) - Zhou, Yuan; Minshall, Tim
Usually, firms that produce innovative global products are discussed within the context of developed countries. New ventures in developing countries are typically viewed as low-cost product providers that generate technologically similar products to those produced by developed economies. However, this paper argues that some Chinese university spin-outs (USOs), although rare, have adopted a novel 'catch-up' strategy to build global products on the basis of indigenous platform technologies. This paper attempts to develop a conceptual framework to address the question: how do these specific Chinese USOs develop their innovation capabilities to build global products? In order to explore the idiosyncrasies of the specific USOs, this paper uses the multiple case studies method. The primary data sources are accessed through semi-structured interviews. In addition, archival data and other materials are used as secondary sources. The study analyses the configuration of capabilities that are needed for idiosyncratic growth, and maps them to the globalisation processes. This paper provides a strategic 'roadmap' as an explanatory guide to entrepreneurs, policy makers and investors to better understand the phenomena.